PENDAPATAN DAN PENGELUARAN RUMAH TANGGA PEDESAAN DAN KAITANNYA DENGAN TINGKAT KEMISKINAN - -, SUPADI; ROZANY NURMANAF, ACHMAD (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006)
Study conducted in 3 province, these are Central Java, Lampung and South Sulawesi. In each province choice 4 villages classified by agroecosystem, i.e wet land villages and dry land villages. In every village interviewed 50-60 households as the Patanas household sample. The purpose of the study is to inform household income, especially per capita income and expenditure that relate to poverty level. This is based on Sayogyo, World Bank and BPS criteria, beside structure and distribution of household income. The result of study showed that according to Sayogyo and BPS criteria household in both agroecosystem, wet land and dry land, are not fall into poverty criteria. But, by using the World Bank criteria the household of the village falls into poverty criteria. While, income structure is still dominated by agricultural sector, but the roll of non-agricultural sector increate gradually. Household income distribution falls in highly inequality classification.
Keywords: Household Income, Expenditure, Poverty, Income Distribution.